Pharmacogenetics in Primary Headache Disorders - Belyaeva, Irina I.; Subbotina, Anna G.; Eremenko, Ivan I.; Tarasov, Vadim V.; Chubarev, Vladimir N.; Schiöth, Helgi B.; Mwinyi, Jessica (Frontiers in Pharmacology, 2022)
Primary headache disorders, such as migraine, tension-type headache (TTH) and cluster headache, belong to the most common neurological disorders affecting a high percentage of people worldwide. Headache induces a high burden for the affected individuals on the personal level, with a strong impact on life quality, daily life management and causes immense costs for the healthcare systems. Although a relatively broad spectrum of different pharmacological classes for the treatment of headache disorders are available, treatment effectiveness is often limited by high variances in therapy responses. Genetic variants can influence the individual treatment success by influencing pharmacokinetics or pharmacodynamics of the therapeutic as investigated in the research field of pharmacogenetics. This review summarizes the current knowledge on important primary headache disorders, including migraine, TTH and cluster headache. We also summarize current acute and preventive treatment options for the three headache disorders based on drug classes and compounds taking important therapy guidelines into consideration. Importantly, the work summarizes and discusses the role of genetic polymorphisms regarding their impact on metabolism safety and effect of therapeutics that are used to treat migraine, cluster headache and TTH exploring drug classes such as NSAIDs, triptans, antidepressants, anticonvulsants, calcium channel blockers, drugs with effect on the renin-angiotensin system and novel headache therapeutics such as ditans, anti-CGRP-antibodies, and gepants. Genetic variants in important phase I, II and III associated genes such as cytochrome P450 genes, UGT genes, different transporter genes are scrutinized as well as variants in genes important for pharmacodynamics and several functions outside the pharmacokinetic and pharmacodynamic spectrum. Finally, the article evaluates the potential and limitations of pharmacogenetics approaches for individual therapy adjustments in headache disorders.